PENGARUH PEMBERIAN SUSU KEDELAI KUNING (Glycine max (L.) Merr.) TERHADAP KADAR KOLESTEROL TOTAL PADA PRIA HIPERKOLESTEROLEMIA - Santi Widiasari; Mutiara , Mutiara Muslimah; Eliya Mursyida (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2023)
Abstract.Hypercholesterolemia is an increase in blood cholesterol levels, which is more than 200 mg / dl. In Indonesia, 9.3% of the incidence of hypercholesterolemia is in productive age, namely the age range of 25-40 years. One of the drugs for hypercholesterolemic sufferers is a statin which is believed to reduce LDL levels and inhibit the formation of cholesterol by indirectly affecting cholesterol levels in the blood. Soybeans are known to reduce cholesterol levels because they contain isoflavones that bind to the endoplasmic reticulum, then increase the Low-density lipoprotein (LDL) receptors in the liver. So that LDL levels in plasma are measured to be low. Objective: To analyze the effect of giving soy milk on cholesterol levels in hypercholesterolemic men. Method: Experimental using the design